Meningkatkan Motivasi Dan Hasil Belajar Siswa Dalam Pembelajaran Seni Tari Pada Masa Pandemi Covid-19 Di SMP N 4 Tarusan - Dia Rahmayanti; Fuji Astuti (SENDRATASIK UNP, 2021)
This type of research is Class Action Research (PTK). This research will be carried out 2 cycles, cycle I is done 2 times and cycle II is done 2 times. The intrument used in this study are motivational questionnaires and student knowledge tests.  This type of data uses primary data and secondary data. Data collection techniques are carried out by means of observation (observation), tests of learning outcomes (tests for work) and tests of student motivation in cultural arts (dance) subjects, then completed with documentation. Data is analyzed using the percentage formula. The results showed that the use of Demonstration Methods and lectures in the learning of cultural arts, especially dance arts in class VIII.3 junior high school N 4 Tarusan, South Coast can increase learning outcomes In addition to the use of Demonstration Methods, Lecture Methods and media can also avoid saturation in students in following the teaching and learning process, so as to foster student motivation, and more fun learning. This is evidenced by the existence of student learning outcomes in class VIII.3 in cycle I of the average student learning outcome of 61.61, with quite good criteria. Furthermore, student motivation towards cultural arts (dance) subjects averaged 53 with unfavorable criteria. In cycle II student learning outcomes increased by an average of 84.51% of excellent criteria. Furthermore, the motivation of students against dance arts subjects averaged 69.00 with quite good criteria. It can be concluded that the selection of strategies using the Demonstration Method, lecture method and media has succeeded in achieving the target above KKM which is 75.